Forex of India since 1991: A Study Based on Mann-Kendall Time Series Trends - V. T. Vasagan (Talaa : Journal of Islamic Finance, 2025)
India's has become the fourth largest country in the foreign exchange reserves. The Foreign Exchange Reserves (FX Reserves) of India refer to the total foreign currency assets held by the Reserve Bank of India (RBI). It includes Special Drawing Rights (SDRs), Physical Gold and Foreign Currency Assets. Foreign Exchange Reserve stabilizes the Indian economy, particularly in terms of foreign trade and payment systems. This study delves a dataset of 31 years from 1991 to 2022. The objective of the investigation is to analyze the long-term trends to gain insight into the dynamics of the Indian economy and explore it association with GDP growth. The Mann-Kendall test is used to analyze trends in time series data and regression to analysis its impact on the growth of GDP of India. The study reveals the Mann-Kendall test that the computed p-value is lower than the significance level 0.05 at 95% of confident level, the null hypothesis is rejected. Hence, the foreign exchange reserve of India increases further and has positive trend. But in respect of GDP it has no impact on the growth of GDP of India since the p-value is greater than the significance level of 0.05 at 95% of confident level. Thus, Government of India has to take new initiatives, policies and strategies to strengthen its Forex reserves. This will enhance macroeconomic stability, and improve its resilience to external shocks in the global economy.